Role of Multi Detector Computed Tomography Cervicocerebral Angiography in Evaluation of Patients with Stroke - Mallula, Balaji Varaprasad; Chintala, Jithender Reddy; Boppanna, Srinadh; S. Annapurna (Asian Journal of Medical Radiological Research, 2020)
Background: Stroke is the second single most common cause of death in the world causing approximately 6.7 million deaths each year. It has a greater disability impact on an individual than any other chronic disease. The aim of the study is to review the value of CTA in detection and evaluation of non-traumatic cervicocerebral vascular disease (stroke). Subjects & Methods: A prospective observational study conducted in the Department of Radiodiagnosis, Kamineni Hospitals, L.B. Nagar, Hyderabad over 60 patients during April 2016 to May 2017. Results: Out of 60 patients, 35(58.3%) patients had ischemic stroke, 25(41.6%) had hemorrhagic stroke. Overall stroke was seen mostly in the age group of 61-70 (28.3%) years, with a Male to female ratio of 3:2. Conclusion: Hypertension was the most common risk factor associated with this disease, followed by diabetes. CTA helps in accurate diagnosis, risk stratification and planning management protocols.